Consumption of Energy Drinks in Medical Students of Nowsera Medical College - Alamzeb Jadoon, Shah Nawaz, Safdar Irfan Marwat, Syeda Khadijah Mahrukh, Zahid Irfan Marwat, Ayesha Gohier, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Young adults use energy drinks that have high caffeine levels. Higher consumption will increase health risk. Effects of different ingredients on health need to be investigated. Consumption of energy drinks has become popular in students but there has been little research regarding energy drink consumption patterns in college students in Pakistan. Aim: To determine energy drink consumption patterns in college students, prevalence and frequency of energy drink use and the perception of students about benefits and hazards of energy drinks consumption. Methods: A cross sectional study was conducted on total of 180 medical students of Nowshera from all years of medical course from Jan 2019 to Dec 2019. 180 medical students were selected through convenient sampling technique. After obtaining verbal consent the data were collected using a self-administered, closed ended questionnaire and analyzed by using SPSS version 20. Results: Frequency of energy drinks consumption was found to be 110(61.1%) in a sample of 180 medical students of MBBS. Sting was the most common brand consumed 73.33% consumed by them. The major reasons reported for its usage were to gain/replenish energy and boost stamina by 46(29.8%), and studying for examination by 25(16.2%). Advertisement 24(15.5%) was reported as the major source of information followed by friends 47(30.5%). Significant differences were found between usage of energy drinks with gender (<0.001), i.e., 79(71.8%) males and 31(28.2%) females. Conclusion: Consumption of energy drinks, despite the variation in the reason for choosing such drinks, is quite common in college students. Consumption rate was high in male gender (63.9%). The main reasons for consumption were to gain/replenish and boost energy and to increase the concentration in studies. A greater percentage (54.6%) of the students were aware of the adverse effects of energy drinks consumption.